Status Kewarganegaraan Warga Negara Indonesia (WNI) Eks Isis Ditinjau Dari Undang-Undang Nomor 12 Tahun 2006 Tentang Kewarganegaraan Republik Indonesia - Ade Idra Suhara; Tunziah Tunziah (UIR Press, 2021)
The background of the problem in this study is that there is a discourse on the repatriation of ex-ISIS Indonesian citizens to Indonesia, causing differences of opinion among the Government over the polemic of the citizenship status of ex-ISIS Indonesian citizens. The purpose of this study was to determine the citizenship status of Indonesian Citizens (WNI) Ex ISIS Judging from Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia. This type of research is qualitative using a normative juridical approach. This research is a library research and data collection techniques are carried out by conducting research on library materials. The primary legal material collection technique that the author uses is by using a study of legislation that is still valid in Indonesia. While the collection of secondary legal materials is carried out by examining several reference sources related to the title of the study (books, journals, news on youtube). The results of the author's analysis state that based on the review of Law Number 12 of 2006, the citizenship status of Indonesian Citizens (WNI) ex ISIS does not automatically lose their citizenship.